Evolution of isoprene emission in Arecaceae (palms). (14th December 2020) - Li, Mingai; Xu, Jia; Lyu, Fuling; Khomenko, Iuliia; Biasioli, Franco; Villani, Mariacristina; Baldan, Barbara; Varotto, Claudio
Abstract: Isoprene synthase (IspS) is the sole enzyme in plants responsible for the yearly emission in the atmosphere of thousands of tonnes of the natural hydrocarbon isoprene worldwide. Species of the monocotyledonous family Arecaceae (palms) are among the highest plant emitters, but to date no IspS gene from this family has been identified. Here, we screened with PTR‐ToF‐MS 18 genera of the Arecaceae for isoprene emission and found that the majority of the sampled species emits isoprene. Putative IspS genes from six different genera were sequenced and three of them were functionally characterized by heterologous overexpression in Arabidopsis thaliana, demonstrating that they encode functional IspS genes. Site‐directed mutagenesis and expression in Arabidopsis demonstrated the functional relevance of a novel IspS diagnostic tetrad from Arecaceae, whose most variable amino acids could not preserve catalytic function when substituted by a putatively dicotyledonous‐specific tetrad. In particular, mutation of threonine 479 likely impairs the open–closed transition of the enzyme by altering the network of hydrogen bonds between helices H1α, H, and I. These results shed new light on the evolution of IspS in monocots, suggesting that isoprene emission is an ancestral trait within the Arecaceae family. The identification of IspS from Arecaceae provides promising novel enzymes for the production of isoprene in heterologous systems and allows the screening and selection of commercially relevant palm varieties with lower environmental impact.